ACTIVE LEARNING MODELS TECHNIQUES LEARNING START WITH A QUESTION TO INCREASE LIVELINESS OF STUDENTS - Nurmawaddah Nurmawaddah (Universitas Negeri Yogyakarta, 2017)
This research is a classroom action research.This study has the objective to increase liveliness of students' in accounting learning class XI Accounting 1 SMK Negeri 1 Yogyakarta Academic Year 2016/2017 use Active Learning Model Techniques Learning Start With A Question. As for the four stages including planning, implementation, observation, and reflection. The research data were collected through observations, documentation, and field notes. Improvement liveliness of students can be seen from the average liveliness of students in the first cycle showed 48.35% of the students have been active and average liveliness of students in the second cycle increased to 78.47%. Increased liveliness of students from the first cycle to the second cycle amounted to 30.12%. Keywords : Learning Start With A Question, liveliness of students.